An emotional journey of identity change and transformation: The impact of study-abroad experience on the lives and careers of Chinese students and returnees - Gu, Qing (Berghahn Journals, 2015)
This article discusses the nature of Chinese students' transnational experiences and its impact on their identities within and beyond national and cultural boundaries. The discussion is located in the theoretical framework of transnationalism and explores in detail the ways in which students adapt, change and develop, both in the host country of their study and also on their return to work in their home countries. Empirical evidence in the article is drawn from the findings of three studies, led by the author, which have investigated the pedagogical, sociocultural and emotional challenges that Chinese students have encountered when studying at British universities, and the perceived impact of their overseas studies on their lives and careers in their home countries. The research findings suggest that there are distinctive patterns of challenges, struggles, adjustments, change and achievement over time – all of which are embedded in the processes of socialisation, enculturation and professionalisation. Such experiences are both transitional and transformational and, most profoundly, they necessitate identity change at and across different layers of boundaries. At the heart of this identity change is a constant, emotional search for a reflexive sense of self as an embodied individual, a member of a professional group and a member of an organisation.